A widely tunable, high power, single-mode laser for linear and nonlinear spectroscopy - Richard, K; Manson, P; Ewart, P (2008)
A laser system based on a modeless laser, acting as a narrow bandwidth amplifier, seeded by a single-mode diode laser is reported with significantly improved performance for continuous scanning over a wide spectral range. A novel arrangement is described for scanning the modeless laser to maintain the peak amplification of the narrow bandwidth amplifier at the frequency of the seeding diode laser as it is tuned in frequency. An error signal is generated by optical pick-up of the displacement of the seeding laser generated by dispersion in the modeless laser. The error signal is used to drive a tuning mechanism to correct the central frequency of the modeless laser to match that of the seed laser. This 'seeding by optical pick-up error correction' is demonstrated to provide continuous single-mode scanning and to correct for mode hops in the master oscillator over a range exceeding 170 cm-1. Application of the system for wide spectral coverage and high-resolution linear and nonlinear laser spectroscopy is illustrated by absorption spectroscopy and polarization spectroscopy of molecular iodine. © 2008 IOP Publishing Ltd.